OCCUPATIONAL SAFETY AND HEALTH MANAGEMENT LITERATURE REVIEW ON IMPLEMENTATION CHALLENGES AND STRATEGIES - Indra Fauzi Umar; Daud Arifin (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
Occupational Safety and Health (K3) is a crucial aspect in creating a safe, healthy, and productive work environment. Although it has been regulated in various national regulations and international standards such as ISO 45001:2018, the implementation of K3 in Indonesia still faces various challenges. This study aims to examine the challenges and strategies for the implementation of K3 management through a literature review approach to eight relevant scientific articles. This study uses a qualitative descriptive method with thematic analysis techniques to identify patterns, constraints, and best practices in the management of K3 in various industrial sectors. The results of the study show that the paradigm shift from an administrative approach to a risk-based strategic approach is the key to the successful implementation of K3. However, structural barriers, weak work culture, and weak supervision are the main obstacles. Some strategies that have proven effective include proactive leadership, risk-based training, open reporting systems, and integration of CSR with quality management systems and the environment. Thus, effective implementation of K3 requires a systemic approach, management commitment, and strengthening regulations to create a safe and sustainable work culture.